Concurrence of multiple sclerosis and amyotrophic lateral sclerosis in patients with hexanucleotide repeat expansions of C9ORF72. Issue 1 (20th October 2012) - Ismail, Azza; Cooper-Knock, Johnathan; Highley, J Robin; Milano, Antonio; Kirby, Janine; Goodall, Emily; Lowe, James; Scott, Ian; Constantinescu, Cris S; Walters, Stephen J; Price, Sian; McDermott, Christopher J; et al.
Abstract : Background: Crossover in the pathogenic mechanisms of amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS) has been described but is poorly understood. A GGGGCC hexanucleotide repeat expansion of C9ORF72 has recently been identified in a significant proportion of patients with ALS. Methods: In approximately 650 patients diagnosed with ALS from the North of England we identified seven patients who initially presented with MS. DNA obtained from five patients with MS-ALS and 215 patients with MS alone was screened for the C9ORF72 expansion. Post-mortem material was examined from two patients with MS-ALS. Gene expression profiling was performed on lymphoblastoid cells and levels of CXCL10 were measured in cerebrospinal fluid (CSF) from patients with ALS with and without the C9ORF72 expansion and controls. Results: Concurrence of MS and ALS is higher than expected in our population. The C9ORF72 expansion was identified in 80% of patients with MS-ALS but not in those with MS alone. In the presence of preceding MS, C9ORF72 -ALS was more rapidly progressive. MetaCore analysis identified alteration of the NF-кB pathway in C9ORF72 -ALS and non- C9ORF72 -ALS. NF-кB activation is associated with increased expression of the neuroprotective cytokine CXCL10 but, in C9ORF72 -ALS, CXCL10 is downregulated and CSF levels are reduced. Conclusions: We propose that MS-associated neuroinflammation may affect penetrance and progression of the C9ORF72 expansion. In particular, the NF-кB pathway is activated in MS and appears to be dysfunctional in C9ORF72 -ALS. Aberrant downregulation of CXCL10 may explain the predisposition of C9ORF72 expansion carriers to develop ALS in the context of MS and NF-кB activation, and offers a potential therapeutic target.